Role and Clinical Significance of LncRNA16 in the Malignant Proliferation of Lung Cancer Cells: LncRNA16 in the Lung Cancer Cells - Gu, Mingming; Chen, Zhubei; Xiong, Hui; Liu, Kun; Ye, Zhangpeng; You, Qingsheng (Cellular and Molecular Biology, 2022)
The highest mortality rate among cancer patients is lung cancer. A large proportion of cancer patients are lung cancer patients. The incidence rate of lung cancer is the highest in the world. In recent years, long-chain non-coding RNA, or LncRNA, has become more and more closely related to cancer and has gradually attracted the attention of many cancer researchers. LncRNA is the proto-oncogene of cancer. We can find out the cause of cancer and put forward effective methods to inhibit the occurrence of cancer by studying LncRNA. This study aimed to investigate the effect of noncoding long-chain RNA16 on the proliferation and molecular mechanism of lung cancer cells. During the operation, the distance between the excised lung cancer block and the adjacent tissue is 2cm from the corresponding lung cancer block. Then, the total RNA in lung cancer cells and tissues is extracted with a Trizole reagent. Then, the expression profile of LncRNA in three cases of lung cancer and the corresponding adjacent tissue is identified by RNA chip technology. The LncRNA related to proliferation and the expression difference is significant through bioinformatics. The conclusion was that the A549 and H1299 groups of shLncRNA16 could significantly reduce the incidence by 64% and 40% percentage points compared with the experimental group, which indicates that LncRNA16 can be used as a potential treatment target for patients.